2019
DOI: 10.1088/2051-672x/ab2038
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the mechanical performance of the electroless Ni–W–P coating based on fractal theory

Abstract: Engineering surface shows fractal characteristics, and mechanical performance of electroless Ni-W-P coating with fractal parameters can avoid the effects of instrument resolution and sampling length. In the present work, the ternary Ni-W-P coatings were deposited on mild steel (1015) polished with various sandpapers. Surface morphology of coating and mechanical property, including matrix roughness, adhesion strength, friction behavior and elastic modulus were investigated by using scanning electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The specific process of flatten modification is as follows: The surface topography of a sub-image is extracted line by line into height sequences. Each height sequence is least-squares fitted by using a polynomial with an order of 1 or 2 (i.e., the flatten order), as shown in Equations ( 4) and (5), respectively. Then the polynomial was subtracted from the height sequence to provide the relative height sequence.…”
Section: Roughness Scaling Extraction (Rse) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific process of flatten modification is as follows: The surface topography of a sub-image is extracted line by line into height sequences. Each height sequence is least-squares fitted by using a polynomial with an order of 1 or 2 (i.e., the flatten order), as shown in Equations ( 4) and (5), respectively. Then the polynomial was subtracted from the height sequence to provide the relative height sequence.…”
Section: Roughness Scaling Extraction (Rse) Methodsmentioning
confidence: 99%
“…The analysis of surface features is of great significance and is widely applied in relevant fields, such as natural geographical topography [1], and in determining various surface morphology performance [2][3][4], and evaluating nanostructured-thin film property [5][6][7]. Zhang et al [8] and Hosseinabadi et al [9] reported a series of analyses on the rough surface of multiscale structures by calculating their fractal dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of thermal physical parameters of micro-scale Ni-W-P coating will be further carried out in our subsequent research. Now, take the thermal conductivity of Ni-W-P coating into the equation We can obtain the thermal conductivity of Ni-W-P coating from Equation (8). Then, the change of it with the variety of ambient temperature, as well as differences of W element content at constant temperature can be analyzed.…”
Section: Recordingmentioning
confidence: 99%
“…where Φ 2 is the heat exchange amount of substrate with Ni-W-P coating, W. δ 2 is the thickness of Ni-W-P coating, m. λ 2 is the thermal conductivity of Ni-W-P coating, W/(m•K). T 3 is the cool side temperature of Ni-W-P coating, K. We can obtain the thermal conductivity of Ni-W-P coating from Equation (8). Then, the change of it with the variety of ambient temperature, as well as differences of W element content at constant temperature can be analyzed.…”
Section: Recordingmentioning
confidence: 99%
See 1 more Smart Citation